Credit Default Swap (CDS) Spreads: The Analysis of Time Series for The Integration with The Interest Rates and The Growth in Turkish Economy - Bilal Kargi (Montenegrin Journal of Economics, 2014)
This text is for the relation between credit default swap (CDS) spreads and some chosen macro economic data in Turkish economy. Credit default swap spread as an insurance spread is the most important sign for the solvency of the debitors in that country about the securities that public sector and companies export in an economy. Thus, the decisions of investors for the investment feasibility related to economy are based on the information that was supplied by these spreads. Therefore, the credit default swap spreads have become a kind of reliability index. Moreover, they have become an information source about the general view of economy except the investee securities. In this study, the relation between the interest rates of CDS spreads and GDP is determined over time.
Keywords: G24; O52; O40; 330; Credit Default Swap Spreads; GDP; CDS; Interest Rates; Turkish Economy